Prevalence of atrial fibrillation in ischemic stroke and associated risk factors: A hospital-based study in Indonesia - Theodore Amadeo Nathan; Raisa Wibowo; Radhitya Sasongkojati; Budhi Hartoko; Debora Theresia Butarbutar (Brain Circulation)
CONTEXT: The prevalence of ischemic stroke increases each year. One such important factor is the presence of atrial fibrillation (AF), but data regarding this are scarce in Indonesia. AIMS: This study aimed to understand the prevalence of AF in ischemic stroke and its associated risk factors. SETTINGS AND DESIGN: A cross-sectional study was conducted from January 2021 to 2023 in Fatima Hospital, through medical records. SUBJECTS AND METHODS: Subjects were ischemic stroke patients aged ≥18 years. Additional data included demographic characteristics, congestive heart failure (CHF), hypertension, diabetes mellitus, stroke history, vascular disease, AF, dyslipidemia, Glasgow Coma Scale, and anticoagulant usage. STATISTICAL ANALYSIS USED: Data were analyzed using Chi-square, Fisher, Student’s t-test, Mann–Whitney, and logistic regression. RESULTS: Out of 148 subjects, AF was detected in 16 (10.8%). Among these, 14 (87.5%) had a CHA2DS2-VASc score of ≥2 and were given anticoagulant therapy. A higher proportion of subjects aged over 75 years was observed in the AF group (31.2% vs. 3.8%; P < 0.001). A similar pattern was seen with CHF and dyslipidemia (CHF: 56.3% vs. 8.3%; P < 0.000; dyslipidemia: 93.7% vs. 58.3%; P < 0.005). CHF and dyslipidemia increased the risk of AF by 27-fold (P = 0.001, odds ratio [OR]: 27.400) and 21-fold (P = 0.013, OR: 21.812), respectively. CONCLUSIONS: These findings underscore the importance of vigilant screening for AF in ischemic stroke, particularly in patients with CHF and dyslipidemia, to guide appropriate anticoagulation therapy and reduce the risk of recurrent stroke. This study was limited by its single-center design and small sample size. A larger, multicenter study is recommended.